Aligning HE Pedagogical Innovation with VET, Industry, and Research Partnerships: Insights on the Demola Portugal Initiative - Susana Amante; Rosina Fernandes (MDPI AG, 2023)
Academia-industry collaboration has been around for some time, but there has been a shift in both the education and workforce settings to work closely together, coordinating initiatives across all sectors, namely higher education (HE), vocational education and training (VET), and industry, in an attempt to mutually drive innovation, provide opportunities to go from concept to action, encourage entrepreneurship, improve ICT use, and other equally important hard and soft skills, aiming to bridge the existing gap between the teaching-learning arena and the business world. Aware that the VET sector, HE, the government, and industry should be devoted to forging partnerships considered key to the development of research, leading to quality, more business, and ultimately, the economic and social well-being of society, a Consortium of 14 Portuguese Polytechnic Institutions engaged in an innovative pedagogical training program, "Learning based on co-creation processes," a project within the Demola Portugal Initiative (2021-2023), and at the Polytechnic Institute of Viseu (IPV) with reference No. POCH-04-5267-FSE-000818. This training program, with its active methodologies, is then put into practice through the "Link Me Up-1000 Ideias" project. In our study, we will focus on the needs, expectations, and experiences of the IPV teaching staff and the vocational schoolteachers that participated in the training course. Through the analysis of questionnaires and e-portfolios of the participants in the first two editions (January-June 2021 and September 2021-February 2022), we intend to answer the following questions: (i) Which facilitation skills can be meaningfully used by the teachers participating in the (Demola) Pedagogical Innovation Training course at IPV? (ii) Which tools/platforms can enhance the students' learning and collaboration among different team members, company representatives, and trainees/facilitators? The data collected confirm that the Demola Portugal Initiative provides an effective approach to bring HE closer to the labor market and keep pace with progress and innovation.